Pengolahan Terbitan Berseri di Perpustakaan STMIK Indonesia Padang - Elvi Marda Tesa; Marlini Marlini (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2013)
The purposes of this research are: (1) processing term-publishment at STMIK Indonesia Padang library, (2) challenging facing in processing term-publishment at STMIK Indonesia Padang library as well as the effort should be conducted in order the term-publishment processing at STMIK Indonesia Padang library better. Data is gained by direct observation as well as interview with the STMIK Indonesia Padang head-library. The data is analyzed using descriptive method. The finding of the research are first the processing of term-publishment at STMIK Indonesia Padang library is conducted by examining the term-publishment coming to the office, allowing an owner-mark, then releasing it into catalog for a journal which it will be put in each place. Second, challenge facing in processing the term-publishment at STMIK Indonesia Padang library is the librarian does not take note the term-publishment data to the invetaris book or registration card as well as the magazine has not been released into catalog. Keywords: processing; term-publishment